Performance Analysis of Grid Integrated Hydro and Solar Based Hybrid Systems. (17th June 2013) - Meshram, Sweeka; Agnihotri, Ganga; Gupta, Sushma
Abstract : The renewable energy systems (RESs) are an attractive option to electrify the community as they are environment friendly, free of cost, and all-pervading. The efficiency of these energy systems is very low and can be improved by integrating them in parallel. In this paper, hydro (7.5 kW) and solar systems (10 kW) are taken as RESs and connected with the utility grid. Due to the intermittent nature of both the hydro and photovoltaic energy sources, utility grid is connected to the system for ensuring the continuous power flow. The hydro power generation system uses the self excited induction generator (SEIG) and converters. The AC/DC/AC converter is used as interface to connect the hydro turbine to the utility grid to adjust the generated voltage to the utility grid voltage. The solar generation system is the combination of PV array, boost converter, and solar inverter. The control of both the hydro and solar power plants is provided through the constant current controller. The analysis has been done to verify the existence of the proposed system. Results demonstrate that the proposed system is able to be put into service and can feed the community.